Why Sanctions Against Russia Work - András Rácz; Ole Spillner; Guntram B. Wolff (Intereconomics, 2023)
Since the annexation of Crimea in 2014, Russia has been under an EU sanctions regime. While these sanctions have not prevented Putin from ordering an invasion of Ukraine in February 2022, in the overall picture, they have significantly weakened Russia's ability to wage war. This paper demonstrates the effectiveness of the sanctions and argues that the EU should maintain and tighten sanctions, thus further weakening the military and economic power of the Putin regime.
Keywords: F5; F51; B17; 330; sanction; economic damage; Russia; Sanktion; Wirtschaftlicher Schaden; Russland